Peran Guru Dalam Membentuk Kecerdasan Spiritual Siswa - Noval Maliki; Hulalul Anbiyaa (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study aims to analyze the role of teachers in shaping students’ spiritual intelligence at Madrasah Tsanawiyah Negeri 3 Cirebon. Employing a qualitative descriptive approach, the study was conducted among Grade VII students. The results indicate that teachers play three main roles in developing students’ spiritual intelligence, namely as role models, religious guides, and motivators. As role models, teachers provide tangible examples through their behavior and acts of worship. As religious guides, they help students understand and practice Islamic teachings. As motivators, teachers encourage students to enhance their faith and piety. Moreover, students’ spiritual intelligence is also influenced by external factors such as family support, the students’ own willingness, and habitual practices in daily life. Thus, an optimal teacher role, supported by a conducive environment, significantly contributes to the strengthening of students’ spiritual intelligence.